Harmonizing Kuranglabih Values in River-Based Traditional Trade: Lok Baintan Floating Market Study - Apriati, Yuli; Budimansyah, Dasim; Pasani, Chairil Faif; Nurdin, Encep Syarief (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
This study examines the integration of local wisdom, Islamic values, and early childhood engagement in the river-based traditional trade at the Lok Baintan Floating Market. The study delves into the enduring